Контроль за перевантаженням на базі теплової моделі асинхронного електродвигуна - Худолій, Сергій Сергійович (НТУ "ХПІ", 2010)
Dependence between maximum admissible current value and temperature models parameters is discussed in this article. Used temperature model also allow for dynamic power loss of electrical motor. This dependence allows to limit maximum current value of induction motor according to variable temperature conduction of electrical machine.
Control of overload using thermal models induction motor
Keywords: електропривод; машина електрична; навантаження; тепловіддача